ĐẶC ĐIỂM THÀNH PHẦN HOÁ, TUỔI VÀ ĐIỀU KIỆN THÀNH TẠO CỦA RUBY, SAPHIR TRONG ĐÁ BIẾN CHẤT ĐỚI SÔNG HỒNG - Nam, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2012)
Chemical composition, age and forming condition of rubies and sapphire in metamorphic rocks of Red River Zone The result of study shown that rubies and sapphire bearing primary rocks in Kinh La and 700 Hill characterized by paragenetic minerals assemblage: plagioclase + K-feldspar + corundum + biotite ± garnet, whose formation related to melting processes of meta-sediments rocks of Day Nui Con Voi formation in amphibolite facies. Ruby-sapphire from primary rocks in Kinh La and 700 Hill areas are common crystal form hexagonal prism and big size. The content of colour elements (Cr, Fe, Ti) in rubies- sapphire of Kinh La and 700 Hill areas are different. For rubies in 700 Hill area are mainly in dark red - dark purple red colour, with high contents of chromium (Cr2O3: 0,081 - 0,426%), medium contents total iron (FeO*: 0,153- 0,29%), low titanium contents (TiO2: 0 - 0,06%). In addition, some samples contained very small amounts of V, Ga, and Si. Meanwhile, sapphires in Kinh La are characterized by opaque pale colour, with high contents of total iron (FeO*: 0,15 - 0,762%), titanium contents varied from very low to medium (TiO2: 0- 0.28%), and low chromium contents (Cr2O3: 0,00 - 0,09%). In addition, some samples contained very small amounts of Si, Ca, Mg, Mn, K and Ni. The formation age of rubies - sapphire and Tan Huong granite complex in the research area about 22-25Ma, correlated with strike - slip stages of Red River Zone.